A framework to address communication issues during requirements engineering process for software development outsourcing - Iqbal, Javed; Ahmad, Rodina; Md Nasir, Mohd Hairul Nizam; Noor, Muhammad Asim (Taiwan Academic Network Management Committee, 2018)
With the advent of global software engineering, Software Development Outsourcing (SDO) has gained momentum. But the failure rate of outsourced software development projects is high. For such projects, Requirements Engineering (RE) involves intensive communication among geographically distributed stakeholders resulting in one of the major causes of the projects' failures. Addressing communication issues during RE is critical for the success of such projects. Therefore, the basic objective of this study is to recommend RE practices for addressing communication issues in such scenarios. Literature review has been performed, questionnaire survey has been completed by involving SDO industry practitioners and their semistructured interviews have been conducted for data gathering. We have: (i) Identified 32 communication issues of RE process for SDO from literature and industry, (ii) Provided 28 relevant RE practices to address such issues. A framework has been proposed that maps the communication issues to relevant RE practices in the form of RE practices' sets to address corresponding issues.